2012
DOI: 10.1055/s-0031-1280470
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Duration of Breastfeeding in the Freiburg Birth Collective, Germany (FreiStill)

Abstract: Purpose: The health benefits of breastfeeding for both infants and mothers are well-documented. The aim of this study was to clarify factors associated with successful breastfeeding. Methods: We performed a prospective, multi-centre cohort study of 443 mothers in person using a standardised questionnaire on postpartum day 1. Women who had started to breast-feed were interviewed by telephone after 3, 6 and 12 months. A statistical analysis was performed using the SAS system. Results: 92?% of women (409/443) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
0
10
0
9
Order By: Relevance
“…26,27 Studies of women in Western countries have reported that being well educated is associated with longer breastfeeding duration. 28,29 This study, however, found that mothers who had completed secondary education or above were more likely to stop breastfeeding before 6 months. The finding is consistent with those in developing countries, where a higher educational level can lead to abandonment of traditional infant feeding practices and therefore less intention to breastfeed.…”
Section: Discussionmentioning
confidence: 62%
“…26,27 Studies of women in Western countries have reported that being well educated is associated with longer breastfeeding duration. 28,29 This study, however, found that mothers who had completed secondary education or above were more likely to stop breastfeeding before 6 months. The finding is consistent with those in developing countries, where a higher educational level can lead to abandonment of traditional infant feeding practices and therefore less intention to breastfeed.…”
Section: Discussionmentioning
confidence: 62%
“…22 Neben den möglichen Verletzungen der Brustwarze und einer schlechten Leerung der Brust kann das unkorrekte Saugverhalten des Neugeborenen auch zu psychischen Belastungen von Mutter und Kind führen. 21 23 Eine weiterführende Begleitung der Mutter durch eine Nachsorgehebamme, aber auch durch Gynäkologen und Pädiater, die dem Stillen gegenüber positiv eingestellt sind, sind dringend notwendig. 23 Reifgeborene, die ausschließlich und nach dem Prinzip ad libitum gestillt werden, d. h. nach Bedarf, holen sich während des Stillens normalerweise das, was sie benötigen.…”
Section: Saugverwirrungunclassified
“…21 23 Eine weiterführende Begleitung der Mutter durch eine Nachsorgehebamme, aber auch durch Gynäkologen und Pädiater, die dem Stillen gegenüber positiv eingestellt sind, sind dringend notwendig. 23 Reifgeborene, die ausschließlich und nach dem Prinzip ad libitum gestillt werden, d. h. nach Bedarf, holen sich während des Stillens normalerweise das, was sie benötigen. Trinken sie bei einer Mahlzeit weniger, so werden sie sich beim nächsten Mal früher melden.…”
Section: Saugverwirrungunclassified
“…Daten hierzu wurden in weniger als einem Drittel der Fälle überhaupt erfasst. Der Anteil der Frauen, die gestillt haben, lag bei 87 %, im Vergleich zu Daten aus der Gesamtbevölkerung von 92 % [37]. Zum Zeitpunkt des postpartalen Diabetesscreenings stillten noch 71 % zumindest teilweise, im Vergleich zu 74 % nach 3 Monaten in der erwähnten Untersuchung [37].…”
Section: Veränderungen Im Diagnosezeitpunkt Nach Neuer Gdm-leitlinie unclassified
“…Zum Zeitpunkt des postpartalen Diabetesscreenings stillten noch 71 % zumindest teilweise, im Vergleich zu 74 % nach 3 Monaten in der erwähnten Untersuchung [37]. In anderen Untersuchungen stillten Müttern mit GDM ebenfalls seltener als junge Mütter ohne GDM [34,37,38]. Literatur…”
Section: Veränderungen Im Diagnosezeitpunkt Nach Neuer Gdm-leitlinie unclassified